PENERAPAN METODE EKSPONENTIAL SMOOTHING DALAM MEMPREDIKSI JUMLAH PESERTA DIDIK BARU DI SMA FAVORIT KOTA PAYAKUMBUH - Marizal, Muhammad; Mutiarani, Fikha (Jurusan Matematika FMIPA Universitas Jember, 2022)
Forecasting is a technique for estimating a value on a particular object in the future by paying attention to past data. This forecasting uses the Exponential Smoothing models because the data used is in accordance with the model. This study aims to predict the number of students in favorite high schools in Payakumbuh based on data obtained from 2014 until 2021 which is grouped into science and social studies classes. Forecasting is done using a Single Exponential Smoothing and Double Exponential models. MAPE results show that the Double Exponential Smoothing model is better at predicting the number of new students than Single Exponential Smoothing. Keywords: Double exponential smoothing, forecasting, single exponential smoothingMSC2020: 62M10